2017
DOI: 10.1186/s12885-017-3723-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to HPV self-sampling and cytology among low-income indigenous women in rural areas of a middle-income setting: a qualitative study

Abstract: BackgroundData is needed about barriers to self-collection of Human Papillomavirus (HPV) samples and cytology among low-income, disadvantaged women living in rural areas of lower-income countries as these women are at increased risk of cervical cancer mortality.MethodsIndividual interviews (n = 29), focus groups (n = 7, 5–11 participants) and discussion groups (n = 2, 18–25 participants) were organized with women from three indigenous ethnic groups residing in rural areas in Mexico, after they were provided wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 41 publications
6
84
1
3
Order By: Relevance
“…The CSi study showed that 50% of the distributed self-samples were returned to the laboratory within 2 weeks, 75% within 45 days, and 90% within 50 days. At 180 days (6 months) 99% of all samples were received [6] , which is also consistent with other study observations [9] , [25] , [26] , [27] , [28] , [29] , [30] . Moreover, the 6 months stability time point also reflect the fact that as a screening service provider we do not control the return date of the brushes, but can only encourage participants to return the brushes using a reminder strategy [6] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The CSi study showed that 50% of the distributed self-samples were returned to the laboratory within 2 weeks, 75% within 45 days, and 90% within 50 days. At 180 days (6 months) 99% of all samples were received [6] , which is also consistent with other study observations [9] , [25] , [26] , [27] , [28] , [29] , [30] . Moreover, the 6 months stability time point also reflect the fact that as a screening service provider we do not control the return date of the brushes, but can only encourage participants to return the brushes using a reminder strategy [6] .…”
Section: Discussionsupporting
confidence: 91%
“…HPV self-sampling is an approach to improve screening coverage by offering screening non-attenders an alternative to the physician taken screening sample [9] , [26] , [27] and thereby overcoming some of the main reported reasons for non-attendance [20] . HPV self-sampling can also facilitate implementation of cervical screening in less favored regions where screening has not previously been a priority and/or where medical infrastructure is less developed [27] , [28] .…”
Section: Discussionmentioning
confidence: 99%
“…However, many individuals do not comply with standard screening guidelines, often for a combination of reasons. For example, poor patient compliance may be caused by lack of time for a clinical visit, embarrassment related to the pelvic exam, and/or previous discomfort or pain during a Pap smear ( 34 , 75 , 76 ). Sociocultural and socioeconomic barriers may also cause women to postpone or decline regular cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…In a study among 1,069 woman in Mexico, women reported that the Pap test caused more discomfort, pain, and embarrassment than self-sampling ( 34 ). In a series of interviews with low-income indigenous Mexican women who were given self-sampling kits, most women identified the need to be screened for cervical cancer, but identified multiple barriers to making a clinic visit; the self-sampling kits were found less embarrassing and less painful than sampling by a healthcare professional ( 76 ). In a questionnaire of 3,049 women in Argentina who were invited to self-sample, most women preferred this method because it interfered much less with their daily responsibilities and was less time-consuming than a visit to a clinic ( 77 ).…”
Section: Women Prefer Self-sampling Over Sampling By a Healthcare Promentioning
confidence: 99%
See 1 more Smart Citation